(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2018)
Architecture of ancient Egypt is criss-crossed by a series of giant projects whose aim was to celebrate the divine nature of the Pharaohs and their rights to eternal afterlife. In many of such projects a complex interplay between idealization of symbols in hieroglyph writings and shaping of built objects and cultural landscapes can be seen. Since the afterlife destination of the Pharaohs was in the sky, astronomy plays a relevant role in understanding this interplay, as it occurs, in particular, in the Khufu project at Giza and in the planning of Akhenaten’s capital at Amarna.